Gaussian vault geometry: digital design and fabrication of scaled prototypes - Sharman, M.; Datta, Sambit (National Yunlin University of Science and Technology, 2009)
This paper reports on three approaches to the translation of Gaussian surface models into scaled physical prototype models. Using the geometry of Eladio Dieste's Gaussian Vaults, the paper reports on the aspects encountered in the process of digital to physical prototype fabrication. The primary focus of the paper is on exploring the design geometry, investigating methods for preparing the geometry for fabrication and constructing physical prototypes. Three different approaches in the translation from digital to physical models are investigated: rapid prototyping, two dimensional surface models in paper and structural component models using Computer Numerical Controlled (CNC) fabrication. The three approaches identify a body of knowledge in the design and prototyping of Gaussian vaults. Finally the paper discusses the digital to fabrication translation processes with regards to the characteristics, benefits and limitations of the three approaches of prototyping the ruled surface geometry of Gaussian Vaults.